Cut that out : contemporary collage in graphic design - DR.ME, ....-; Doyle, Ryan, ....-; Edwards, Mark, ....- (London : Thames & Hudson, 2021)
Curated by Ryan Doyle and Mark Edwards, who work together under the name of DR.ME, Cut That Out focuses on the compositions of 50 leading designers and studios from 15 different countries for whom collage has been the key to creating vibrant, effective work – among them Hort, Paul Sahre and atelier bingo. As well as the diverse, cutting-edge work featured throughout, each profile includes a Q&A with the artist that serves to both put the work in context and highlight the visual differences between each designer by exploring their varying methods and attitudes towards to Cut That Out is a rich seam of inspiration to be mimed by all students and graphic designers who wish to explore the creative possibilities of collage in their work.
Keywords: Toegepaste grafiek